Wholesome dwellings : housing need in Oxford and the municipal response, 1800-1939 - Graham, Malcolm, 1948- (Archaeopress Archaeology, 2020)
This study by Malcolm Graham, a leading Oxford local historian for many years, provides an insight into post-war housing needs in Oxford, and how the modern city evolved away from the university buildings and college quadrangles for which the city is internationally renowned.